Effects of Moringa oleifera Leaf Meal Supplementation on Growth Performance and Feed Efficiency of Slow-Growing Broiler - Sugiarto Sugiarto; Nuun Marfuah; Aynan Hismafanti Gunawan (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2026)
Stunting syndrome in broilers is a growth disorder characterized by reduced feed efficiency, slow weight gain, and higher mortality, often caused by digestive disturbances and poor nutrient absorption. Moringa oleifera leaves are rich in protein, vitamins, minerals, and bioactive compounds with antioxidant and antibacterial properties, making them a potential natural supplement to enhance growth and health in stunted chickens. This study aimed to evaluate the effect of Moringa oleifera leaf meal supplementation on the growth performance of broilers experiencing stunting syndrome. A total of 100 one-day-old broiler chicks diagnosed with stunting syndrome were reared for five weeks and assigned to five dietary treatments containing 0, 4, 6, 8, and 10% Moringa oleifera leaf meal in a Completely Randomized Design (CRD) with four replications, each consisting of five birds. Parameters observed included feed consumption, body weight gain, feed conversion ratio, performance index, and mortality rate. Data were analyzed using Analysis of Variance (ANOVA), and means were compared using Duncan’s Multiple Range Test (DMRT). Results showed that Moringa oleifera supplementation had a highly significant effect (P<0.01) on feed consumption, body weight gain, performance index, and mortality, but no significant effect (P>0.05) on feed conversion ratio. It can be concluded that the dietary inclusion of 8–10% Moringa oleifera leaf meal effectively improves growth performance and survival rate in stunting-affected broilers.